Futures Markets and Production Decisions - Marcus, Alan J.; Modest, David M. (Journal of Political Economy, 1984)
This paper investigates the use of futures prices in making production decisions. We derive a preference-independent production rule for firms that face both demand and production uncertainty. This rule is compared to a simple "marginal cost equals future price" rule, which previously has been suggested for firms with deterministic output. Data for agricultural producers are used to examine the importance of output uncertainty in the determination of the proper production rule. Our analysis suggests that for many crops the simple rule is sufficiently accurate to be a useful guide to production.